Towards Equitable Access to Justice Through the Provision of Legal Aid as A Form of Law Enforcement and Human Rights in Indonesia - Ryan Abdul Muhit; Agus Supriyanto (Veteran Law Review, 2022)
The provision of legal aid is a call from the side of the humanitarian aspect to help fellow human beings. This study aims to determine the legal aspects of providing legal aid as a form of law enforcement and human rights in Indonesia in order to achieve equitable access to justice. The method used in this research is normative juridical, with a library research approach. Data collection uses secondary data with qualitative descriptive data analysis methods. The results of this study, namely the provision of legal aid in essence in law enforcement is one of the factors in realizing law enforcement in Indonesia, namely upholding the values of truth and justice as one of the legal ideals based on equality before the law. The provision of legal aid is also an interpretation and implication of the principles of human rights itself, namely equality and the prohibition of discrimination.